Sex Differences in Onset and Progression of Cerebral Amyloid Angiopathy. Issue 2 (24th January 2023) - Koemans, Emma A.; Castello, Juan Pablo; Rasing, Ingeborg; Abramson, Jessica R.; Voigt, Sabine; Perosa, Valentina; van Harten, Thijs W.; van Zwet, Erik W.; Terwindt, Gisela M.; Gurol, M. Edip; Rosand, Jonathan; Greenberg, Steven M.; et al.
Abstract : Background: Cerebral Amyloid Angiopathy (CAA) disease course is highly variable even in hereditary forms. Sex may be a possible modifying factor. We investigated biological sex differences in clinical disease course and magnetic resonance imaging-markers in sporadic (sCAA) and Dutch-type hereditary CAA (D-CAA). Methods: Patients with D-CAA and sCAA were included from hospital and research databases of the Leiden University Medical Center (2012–2020) and Massachusetts General Hospital (1994–2012). Key outcomes were: sex differences in symptomatic intracerebral hemorrhage (sICH) onset, recurrence and survival (analyzed using Kaplan Meier survival and regression analyses), and sex differences in magnetic resonance imaging-markers in D-CAA (explored using scatterplots), and in sCAA (investigated using regression analysis). Results: We included 136 patients with D-CAA (mean age 57 years, 56% women, 64% with previous sICH) and 370 patients with sCAA (mean age 76 years, 51% women, all with previous sICH). Men and women with D-CAA did not differ for sICH onset (median age 54 in men and 56 in women [ P =0.13]). Men with D-CAA had a slightly higher number of sICH compared with women (median 2 versus 1; adjusted RR, 1.5 [95% CI, 1.1–1.9]) and a shorter interval between the first and second sICH (median 1.8 years for men and 3.1 years for women, P =0.02). Men with sCAA had their first sICH at an earlier age (median 75 versus 78 years, respectively, P =0.003) and more lobar microbleeds (median 1 versus 0, P =0.022) compared with women with sCAA. No substantial differences were found in the other magnetic resonance imaging markers. Survival after first sICH was comparable between sexes for D-CAA ( P =0.12) and sCAA ( P =0.23). Conclusions: Men with CAA seem to have an earlier onset (sCAA) and more hemorrhagic disease course (sCAA and D-CAA) compared with women. Future studies are necessary to confirm these findings and determine the underlying role of sex-related factors.